The effects of using familiar melodies in melodic interval identification in undergraduate music majors / Nur Lina Anuar - Nur Lina, Anuar (2015)

(untitled)
Melodic dictation is an important part of most university-level aural skills curriculum. This skill is well esteemed for its ability to facilitate students translate the pitches and rhythms that they hear and visualize them on manuscript. Studies attempting to discover trends in strategy usage of successful dictation takers, however, have not yielded meaningful results. This study attempts to discover whether the use of familiar melodies in interval identification is effective for undergraduate music majors. Control and experimental groups consisted of 60 random samples in each group. Control group will receive no melodic reference to identify intervals, while the treatment group will be trained to identify intervals using familiar melodies. Both groups will then be assessed with 12 intervals using pencil and manuscript with melody being played on a piano. The identified and dictated answers in the span of the experiment serve as test results and data analysis to determine the effectiveness of using familiar melodies in interval identification.